Developmental state of Africa in practice looking east with focus on South Korea - Kayizzi-Mugerwa, Steve (London Routledge, 2020)
This book is the product of research undertaken at the African Development Bank (AfDB) on the lessons that the continent of Africa can draw from the role of the state in Asians rapid economic development in the last 50 years. The book applies a cross-national comparative framework to analyse Africa?s performance drawing broadly on the developmental states of Asia (i.e. Japan, China, India, Vietnam, etc.) with focus on South Korea. The book argues that for Africa to replicate Asia?s developmental success, it may require more than just tweaking the public sector machinery. Dedicated institutions and a citizenry capable of demanding accountability from governments must become key ingredients of the development strategy.
Includes Index
Keywords: Economic development -- Africa; Economic development -- Korea (South) -- Case studies; Economic development -- Government policy -- Africa; Africa -- Economic conditions